The Influence of the Non-Cash Payment System on the Money Supply in Indonesia - Christien Panjaitan (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2021)
This study aims to determine the effect of using a non-cash payment system on the money supply in Indonesia. This research uses quantitative research. The data used in this study is secondary data with a period of 7 years. The method used in this research is Multiple Regression Analysis. The variables in this study are the money supply (M1) as the dependent variable and the number of debit card, credit card, and electronic money transactions as the independent variable. The results of this study are debit card transactions have a positive and significant effect on the money supply, credit card transactions have a negative and significant effect on the money supply, and electronic money transactions have a positive and significant effect on the money supply.